ĐK:.....⇔√9−5x−2−(√x−1)−(x2−1)=0⇔−5(x−1)√9−5x+2−(√x−1)−(x−1)(x+1)=0$\Leftrightarrow (\sqrt{x}-1)(\frac{-5(\sqrt{x}+1)}{\sqrt{9-5x}}-1-(\sqrt{x}+1)(x+1))=0$$\Leftrightarrow x=1(tmđk)$ Cái trong ngoặc sau luôn nhỏ hơn 0Vậy.......
ĐK:.....⇔√9−5x−2−(√x−1)−(x2−1)=0⇔−5(x−1)√9−5x+2−(√x−1)−(x−1)(x+1)=0$\Leftrightarrow (\sqrt{x}-1)(\frac{-5(\sqrt{x}+1)}{\sqrt{9-5x}}-1-(\sqrt{x}-1)(x+1))=0$$\Leftrightarrow x=1(tmđk)$ Cái trong ngoặc sau luôn nhỏ hơn 0Vậy.......
ĐK:.....
⇔√9−5x−2−(√x−1)−(x2−1)=0⇔−5(x−1)√9−5x+2−(√x−1)−(x−1)(x+1)=0$\Leftrightarrow (\sqrt{x}-1)(\frac{-5(\sqrt{x}+1)}{\sqrt{9-5x}}-1-(\sqrt{x}
+1)(x+1))=0$$\Leftrightarrow x=1(tmđk)$ Cái trong ngoặc sau luôn nhỏ hơn 0Vậy.......